PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) SEBAGAI UPAYA UNTUK MENINGKATKAN KEMAMPUAN BERFIKIR KRITIS MAHASISWA TERHADAP LINGKUNGAN SEKITAR - Mukharomah, Ervina; Hidayat, Saleh (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2017)
This research is descriptive research, as for the purpose of this research to improve students' critical thinking ability to environmental problem by using Problem Based Learning (PBL) learning model in Environmental Science subject in Biology Education Study Program of UM Palembang. The study was conducted from September to December 2016. The results of this study indicate that PBL learning model is suitable to be applied in the subject of Environmental Knowledge. That students are able to think critically is seen from the way students solve environmental problems properly, meticulously, logically and thoroughly